Ultra wide to narrow band agile reconfigurable frequency microstrip slot antenna - Abdul Majid, Hairudin (2012)
A simulation of reconfigurable frequency antenna is presented. The antenna is an integration of ultra-wide band antenna with a microstrip slot antenna. It has a capability to operate in ultra-wide band (0.98-12.0 GHz) and seven different narrow bands from 2 GHz to 4 GHz. Seventeen switches with eight configuration are used to select between ultra-wide band and the narrow bands. The proposed antenna demonstrates frequency agility which useful for future communication systems such as cognitive radios.